Management of Village Revenue and Expenditure Budget in Desa Selomarto Kecamatan Giriwoyo Kabupaten Wonogiri - Nasyia Afria Larasati; Sri Suwitri (Journal of Public Policy and Management Review, 2019)
The lateness of Desa Selomarto in sending draft of village regulatio about village revenue adn expenditure budget and the report on the realization of the implementation of the villagerevenue and expenditure budget, are become the background of this study. The purrpose of this study is to describe and analyze the management of village revenue and expenditure budget in Desa Selomarto. In addition, the purpose of this study are to describe, identify and analyze the supplementary and the inhibition factors in managing the village revenue and expenditure budget in Desa Selomarto. This study uses actuating teory according to Syafiie and Hasibuan where variables which taken are communication, supervision, and leadership with a qualitative approach. The technique which uses to collect the data are interview, obersevation, and documentation. The selection of informants usess purposive sampling technique. The result of the study shows that the the principles, functions, structure, implementation, administration, reporting, and accountability of village income and expenditure budgets have not been fully implemented. Futhermore, factors which inhibit the management of village revenue and expenditure budget in Desa Selomarto arethe inaccuracy of supervision, the ineffective leadership style of the Village Head of Selomarto and the low quality of village officials. While the supporting factor is communication within the organization. The recommendation which given by the researcher are the need for changers in the focus of attention in supervision, changes in the leadership style for the Village Head of Desa Selomarto and the more intensense of assistance village official.